Plano de Negócio - P&C Polishing And Cleaning - ALEXANDRE, Maria Aparecida Vieira; MOURA, Aline Salvador Ferreira; TABOZA, Nickollas Gonçalves de Sousa (137, 2023)
Este trabalho de graduação visa analisar a viabilidade de abertura de uma empresa de restauração de mármores e granitos, por meio da elaboração do seu plano de negócio. A metodologia, baseia-se em pesquisa exploratória que tem como objetivo explorar os cenários e a pesquisa descritiva que são recolhidas informações mais específicas e detalhadas do tema. Os resultados sugerem que o empreendedor obtenha bons resultados na abertura do negócio assim consolidando no mercado.

This undergraduate work aims to analyze the feasibility of opening a marble and granite restoration company, through the preparation of its business plan. The methodology is based on exploratory research that aims to explore scenarios and descriptive research that collects more specific and defined information on the topic. The results suggest that the entrepreneur obtained good results in opening the business, thus consolidating himself in the market.
Business Plan - P&C Polishing And Cleaning
Keywords: Gestão de negócios; Negócios - Plano; Gestão e Negócios